PENGEMBANGAN MEDIA VISUAL FLASHCARD BERBASIS ADOBE PREMIERE DI SEKOLAH DASAR - Arum Fatayan; Zulherman Zulherman; Sahla Weny Triannisa (Universitas Labuhanbatu, 2022)
This study aims to produce a visual flashcard learning media for fourth grade elementary school students, as well as to determine the quality of the flashcard product that has been produced so that it is suitable for use in learning Natural Sciences. This research is a research and development (R&D) adapted using the ADDIE development model. There are 5 stages in ADDIE, including: 1) Analysis, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. Validation was carried out by media experts, material experts, as well as due diligence on 3 teachers in different schools. The media created were tested by students as many as 81 students. The results show that the visual flashcard media in Natural Science learning that has been made based on the assessment of students in the software aspect is 88% with very good scoring criteria, material aspect is 89% with very good scoring criteria and 89% in visual communication aspect with very good scoring criteria. good.